Personal financial management skills Of university students and their financial experiences during the Covid-19 pandemic - Lilian Gumbo; Margaret Mutengezanwa; Munyaradzi Chagwesha (Goodwood Publishing, 2023)
Purpose: The main purpose of this study was to assess university students’ financial management skills and their financial experiences during the Covid-19 pandemic.